Re-evaluating Palermo: The case of Burmese women as Chinese brides - Hackney, Laura K (Anti-Trafficking Review, 2015)
The definition of human trafficking as set in the Trafficking Protocol (also known as the Palermo Protocol) functionally centres most of the response to the phenomenon in the criminal justice system. This occludes many of the sociopolitical determinants of vulnerability that leads to trafficking. It also discourages any real debate about the various forms of oppression and even structural violence that act as catalysts to the human trafficking market. The Trafficking Protocol, and a vast number of international organisations, non-governmental organisations and governments, focuses on statistics of prosecution rates, arrests, victim typology and organised crime. I use the example of bride trafficking along the Sino-Burmese border to illustrate the complications and, in certain instances, harm that befall an anti-trafficking regime that does not use a wider lens of migration, agency, development and gender equality to address the factors leading to exploitation.